Comparative study of biological activity of fluorinated 5- aminopyrazoles on Spodoptera frugiperda - Plem, Silvana Cristina (2016)
Several derivatives aminopyrazoles, which are a new class of synthetic insecticide agents, have shown biological activity against lepidopteran, such as Spodoptera frugiperda. The aim of this work was to assess the biological activity of these synthesized compounds. For this purpose, derivatives of 5-amino-1-aryl-1H-pyrazole-4-carbonitriles were synthesized from commercially available aryl hydrazines and (ethoxymethylene)malononitrile. Three compounds (A, B, C) were tested for in vitro biological activity; two of them, A [5-amino-1-(2,6-dichloro-4-(trifluoromethyl)phenyl)-1H-pyrazole-4-carbonitrile] and B [5-amino-1-(perfluorophenyl)-1H-pyrazole-4-carbonitrile] showed promising activity, particularly the compound A.